2014
DOI: 10.4314/ahs.v13i4.23
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with injuries among first-division Rwandan female soccer players

Abstract: Background: Female soccer has grown tremendously in the last decade. Studies have suggested that female soccer players are more susceptible to injuries than their male counterparts, and their vulnerability is due mainly to intrinsic factors such as their anatomical and physiological structure. Objectives: To establish factors associated with soccer injuries among first-division Rwandan female soccer players. Methods: In a descriptive cross-sectional study, self-administered questionnaires were used to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…One prospective study (level II) investigated ‘any injury’ regarding total days injured [ 104 ], whereas the remaining studies examined any physical injury that occurred during sport using either prospective (level II) [ 64 , 66 68 ], case-control (level III) [ 84 ], or cross-sectional study designs (level III) [ 70 , 76 , 102 ]. Two cross-sectional studies (level III) examined participants’ one-season [ 102 ] or three-season [ 76 ] history of ‘any injury’. Sports represented included rugby union, soccer, volleyball, basketball, and softball.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One prospective study (level II) investigated ‘any injury’ regarding total days injured [ 104 ], whereas the remaining studies examined any physical injury that occurred during sport using either prospective (level II) [ 64 , 66 68 ], case-control (level III) [ 84 ], or cross-sectional study designs (level III) [ 70 , 76 , 102 ]. Two cross-sectional studies (level III) examined participants’ one-season [ 102 ] or three-season [ 76 ] history of ‘any injury’. Sports represented included rugby union, soccer, volleyball, basketball, and softball.…”
Section: Resultsmentioning
confidence: 99%
“…Despite significant relationships demonstrating players with increased joint mobility, joint laxity, or muscular flexibility were at an increased risk of sports injury [ 61 , 73 , 76 , 78 , 80 , 95 , 100 , 101 , 104 ], no association summary conclusions with primarily moderate certainty were consistently demonstrated between flexibility and all injury categories in female, team ball sport players. The lack of association between flexibility and sports injury supports the results of several studies that have included stretching exercises in injury prevention programs, but found no significant reduction in injury rates [ 105 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is vital to identify risk factors and injury mechanisms to establish potential preventative strategies [61]. Previous injury is widely documented as a key intrinsic risk factor for future injury in both youth [62][63][64] and senior [65][66][67][68][69] players. An increased injury risk of 74% has been reported in youth players with a history of at least one previous injury [70].…”
Section: Risk Factorsmentioning
confidence: 99%
“…22 Injuries too are serious in South Africa. 23 A review of injuries at two hospitals in Eastern Cape showed that interpersonal violence (60%) and traffic accidents (19%) were the leading causes of injury. One would have thought that hearing loss might not be such an important topic.…”
Section: Nodding Syndrome (Ns) Still An Enigmamentioning
confidence: 99%